Successful Innovation - Syrett, Michel; Lammiman, Jean (London, 2002)
- Successful Innovation From the Publisher Successful innovation is crucial to a business's competitive edge, even its survival, but study after study reveals that many organisations are failing to tap the potential of their staff. This book pinpoints and describes the processes and capabilities required by organisations to foster creative thinking and, equally important, to capture and shape the resulting output. Its findings are based on original research conducted by the authors and work done by leading business professors in America, Europe and Asia. Companies and organisations featured in the book include Kvaerner, British Airways, BMW, software design firm Integrysis, Glaxo-Wellcome, the National Theatre, Japanese cosmetics company Shiseido, French hotel and catering group Accor and Chinese software firm Oticon. Chapters look at: what inspires and informs original ideas; the role of champions and teams in getting ideas off the ground; the importance of continuous evaluation and testing of ideas throughout their development, together with the free flow of information; the roles of consultants and specialists and the crucial factor of leadership. Author Biography: Michel Syrett is a well-known writer, lecturer and consultant on management issues. Together with Jean Lammiman he runs the Innovation in Organisations program at Roffey Park Management Institute. Synopsis Successful innovation is crucial to a business's competitive edge, even its survival, but study after study reveals that many organisations are failing to tap the potential of their staff. This book pinpoints and describes the processes and capabilities required by organisations to foster creative thinking and, equally important, to capture and shape the resulting output. Its findings are based on original research conducted by the authors and work done by leading business professors in America, Europe and Asia.
Keywords: Innovation